The Efforts to Increase Student Activities and Learning Outcomes through the Application of the Cooperative Learning Model with TPS (Think Pair Share) Type - Nur Azizah; Tri Novita Irawati; Sholahudin Al Ayubi (Universitas Islam Jember, 2020)
The aim of the research is to improve student activity and learning outcomes through the cooperative learning model with TPS (Think Pair Share) type. The kind of the research is classroom action research (CAR). The subjects the research were students of class VIII in MTs Walisongo 3. Data collection methods used was tests, observation, interview, and documentation methods. This research was conducted in two cycles, namely cycle I and cycle II. Based on the results of the research conducted, the percentage of activity in the first cycle it reached 67.24% and in the second cycle it reached 73.03%, it appears that there is an increase. Then for the percentage of completeness of learning outcomes in cycle I reached 42.11% and in cycle II reached 94.74%, it appears that there is an increase. Based on the results obtained, it can be concluded that the application of the cooperative learning model with TPS (Think Pair Share) type can increase student activity and learning outcomes. Keywords: activity, learning outcomes, TPS